2006
DOI: 10.1158/0008-5472.can-05-4019
|View full text |Cite
|
Sign up to set email alerts
|

Akt-Mediated Phosphorylation and Activation of Estrogen Receptor α Is Required for Endometrial Neoplastic Transformation in Pten+/− Mice

Abstract: PTEN is a tumor suppressor gene frequently mutated in human cancers. In vitro and in vivo studies have shown that PTEN can exert its tumor suppressive function through a variety of mechanisms, including regulation of cell death and cell proliferation. However, it is still unclear which of the many downstream pathways are critical in each different tissue, in vivo. Loss of PTEN is the earliest detectable genetic lesion in the estrogen-related type I (endometrioid) endometrial cancer. Pten +/À mice develop endom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
82
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 95 publications
(88 citation statements)
references
References 24 publications
6
82
0
Order By: Relevance
“…Moreover, unopposed oestrogen signalling, a well-recognized risk factor for EEC (Amant et al, 2005;Shang, 2006), has been shown to enhance PI3K/Akt activity through binding of oestrogen receptor a (ERa) to the p85a regulatory subunit of PI3K . Conversely, recent studies in heterozygote Pten þ /À mice, which develop EECs with full penetrance, demonstrated that enhanced PI3K/Akt signalling leads to targeted phosphorylation of ERa on Ser167 and ligand-independent activation, thus mimicking a hyperestrogenic environment (Vilgelm et al, 2006). Furthermore, FOXO1 engages in the transcriptional cross-talk with ERa through physical interaction (Schuur et al, 2001), suggesting an important role for FOXO1 in mediating oestrogen responses in target tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, unopposed oestrogen signalling, a well-recognized risk factor for EEC (Amant et al, 2005;Shang, 2006), has been shown to enhance PI3K/Akt activity through binding of oestrogen receptor a (ERa) to the p85a regulatory subunit of PI3K . Conversely, recent studies in heterozygote Pten þ /À mice, which develop EECs with full penetrance, demonstrated that enhanced PI3K/Akt signalling leads to targeted phosphorylation of ERa on Ser167 and ligand-independent activation, thus mimicking a hyperestrogenic environment (Vilgelm et al, 2006). Furthermore, FOXO1 engages in the transcriptional cross-talk with ERa through physical interaction (Schuur et al, 2001), suggesting an important role for FOXO1 in mediating oestrogen responses in target tissues.…”
Section: Discussionmentioning
confidence: 99%
“…18 Loss of PTEN in mouse endometrium has lead to increased phosphorylation of estrogen receptor-a, which resulted in activation of this nuclear receptor even in the absence of ligand, leading to enhanced ability to activate the transcription of its target genes, and therefore contribute to the neoplastic transformation of the endometrial cells. 53 Even though PTEN mutations are frequently present in tumors with MSI, little is known about the interrelation between MSI and estrogen exposure. MSI positive colon cancers have been associated with very low levels of estrogen receptors, 54 while studies in breast carcinoma have yielded controversial results.…”
Section: Discussionmentioning
confidence: 99%
“…Evidences have shown that E 2 induced the phosphorylation of AKT (S473) through PI3K as well as estrogen receptor alpha (ERa; Guo et al 2006). Furthermore, loss of PTEN has been shown to activate AKT, which in turn is responsible for the phosphorylation of ERa on S167; this phosphorylation subsequently activates it (Vilgelm et al 2006). As stated previously, chemoresistance is a major challenge in the treatment of EC.…”
Section: R91mentioning
confidence: 94%